2018
DOI: 10.1039/c8cp01782d
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of hydrous species in amorphous calcium/magnesium carbonates

Abstract: Amorphous calcium carbonate (ACC) is commonly found in many biological materials. As ACC readily crystallizes into calcite, stabilizers, such as anions, cations or macromolecules, often occur to avoid or delay unwanted crystallization. In biogenic ACC, magnesium is commonly present as one of the stabilizing agents. It is generally thought that the presence of mobile water in ACC is responsible for its limited stability and that the strong interaction of Mg2+ with water stabilizes the amorphous structure by ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…Yang et al (53) found that Mg-ACC actually consists of two types of carbonates, amorphous CaCO 3 and amorphous MgCO 3 . Using quasi-elastic neutron scattering, Jensen et al (54) recently observed that water diffuses in amorphous MgCO 3 with similar dynamics to that found for water in clays, although they did not report higher water mobility in Mg-ACC than in pure ACC. All these results are consistent with the conclusion that incorporation of Mg 2+ into ACC introduces relatively unstable sites in the ACC structure, increasing the possibility of ion rearrangement, thus enhancing the probability of structural transformations.…”
Section: mentioning
confidence: 70%
“…Yang et al (53) found that Mg-ACC actually consists of two types of carbonates, amorphous CaCO 3 and amorphous MgCO 3 . Using quasi-elastic neutron scattering, Jensen et al (54) recently observed that water diffuses in amorphous MgCO 3 with similar dynamics to that found for water in clays, although they did not report higher water mobility in Mg-ACC than in pure ACC. All these results are consistent with the conclusion that incorporation of Mg 2+ into ACC introduces relatively unstable sites in the ACC structure, increasing the possibility of ion rearrangement, thus enhancing the probability of structural transformations.…”
Section: mentioning
confidence: 70%
“…Although there are several possible mechanisms by which Mg 2+ modifies CaCO 3 nucleation and affects the subsequent mineral growth (i.e. kinetic blocking of active growth sites due to Mg 2+ adsorption 68 , reduced thermodynamic stability and increased solubility due to Mg 2+ incorporation in the lattice 69,70 , or kinetic stabilization of metastable CaCO 3 polymorphs 71,72 ), there is a general agreement that Mg 2+ hinders the nucleation of calcite and reduces calcite growth rates. This is in line with our findings, with greatly delayed PFs in the presence of Mg 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…This “crystallization of ACC by solid-state transformation” is interpreted here using a reduced activity for the water component. Past investigations of water mobility within ACC have shown deviations with respect to the behavior of bulk water, justifying this approach. , In this sense, the solid-state transformation is understood as a structural reorganization mediated by the presence of water.…”
Section: Discussionmentioning
confidence: 96%
“…Different structural environments for water in ACC have been reported that can be classified mainly as adsorbed and structural molecular water and as hydroxyl groups in more basic and Mg 2+ -bearing ACC. Water in ACC has also been shown to be at least partially responsible for the kinetic persistence of its amorphous structure, via the formation of a hydrogen bond network of water molecules and carbonate ions . The diffusive dynamics of both the hydrous and ionic components of ACC have been studied using X-ray and neutron scattering techniques showing a highly dynamic environment compared with, for example, covalent or metal glasses. , The nanoscale dynamics have been related to the crystallization kinetics of ACC, showing how the presence of foreign ions can affect water dynamics, enhancing its kinetic persistence . X-ray photon-correlation studies of ACC and Mg 2+ -doped ACC have shown that there is a direct proportionality between the Mg 2+ concentration and the frequency of structural rearrangements undergone by structural entities within the amorphous material .…”
Section: Introductionmentioning
confidence: 99%